Repeated-Dose Toxicity of Lauric Acid and Its Preventive Effect Against Tracheal Hyper-Responsiveness in Wistar Rats with Possible In Silico Molecular Targets - Indyra Alencar Duarte Figueiredo; Alissa Maria de Oliveira Martins; Alexya Mikelle Teixeira Cavalcanti; Jayne Muniz Fernandes; Ludmila Emilly da Silva Gomes; Mateus Mendes Vieira; Gabriel Nunes Machado de Oliveira; Isabela Motta Felício; Lucas Nóbrega de Oliveira; Igor Gabriel da Silva Ramalho; Natália Ferreira de Sousa; Luciana Scotti; et al. (Pharmaceuticals, 2025)
Background/Objectives: Lauric acid (LA), a medium-chain fatty acid, is a promising drug for asthma treatment. This study evaluated the toxicity of repeated doses and the effect of LA on pulmonary ventilation and tracheal reactivity in asthmatic Wistar rats and identified possible molecular targets of LA action in silico. Methods: The rats were divided into control (CG) and LA-treated groups at 100 mg/kg (AL100G) for toxicity analysis. Pulmonary ventilation and tracheal reactivity were assessed in the control (CG), asthmatic (AG), asthmatic treated with LA at 25, 50, or 100 mg/kg (AAL25G, AAL50G, and AAL100G), and dexamethasone-treated groups (ADEXAG). Results: The results showed that LA at a dose of 100 mg/kg did not cause death or toxicity. A pulmonary ventilation analysis indicated that AG had reduced minute volume, which was prevented in AAL25G. LA at all doses prevented carbachol-induced tracheal hyper-responsiveness and reduced the relaxing effect of aminophylline, as observed in AG. An in silico analysis revealed that LA had a good affinity for nine proteins (β2-adrenergic receptor, CaV, BKCa, KATP, adenylyl cyclase, PKG, eNOS, iNOS, and COX-2). Conclusions: LA at 100 mg/kg has low toxicity, prevents hyper-responsiveness in an asthma model in rats, and acts as a multitarget compound with a good affinity for proteins related to airway hyper-responsiveness.